NEED TO BELONG DAN OF MISSING OUT MAHASISWA PENGGUNA MEDIA SOSIAL INSTAGRAM - Shodiq, Fajar; Kosasih, Engkos; Maslihah, Sri (Program Studi Psikologi Universitas Pendidikan Indonesia, 2020)
This research is to find the correlation between need to belong and fear of missing out in college instagram user in Bandung city. Quantitative research method used in this research with participant of 324 college student in Bandung city. The instrument in this research was using need to belong and fear of missing out scale made by Wibowo and Santika that adapted from the aspects of need to belong and fear of missing out by Baumeister and Leary for the need to belong scale, and Pryzblzski, Murayama, DeHaan, and Gladwell for measuring fear of missing out. This research made data analysis simple correlation. Result showed that there is positive correlation between need to belong and fear of missing out with adjustment of 0.327.